A pandemic within other pandemics. When a multiple infection of a host occurs: SARS-CoV-2, HIV and mycobacterium tuberculosis - González-Doménech, Carmen María; Pérez Hernández, Isabel Ascensión; Gómez Ayerbe, Cristina; Viciana-Ramos, María Isabel; Palacios-Muñoz, María Rosario; Santos-González, Jesús Leandro (My University, 2021)
By the middle of 2021, we are still immersed in the coronavirus disease 2019 (COVID-19) pandemic, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The concurrence of this new pandemic in regions where human immunodeficiency virus (HIV) and tuberculosis (TB) infections possess the same epidemiological consideration, has arisen concerns about the prognosis, clinical management, symptomatology, and treatment of patients with triple infection. At the same time, healthcare services previously devoted to diagnosis and treatment of TB and HIV are being jeopardized by the urgent need of resources and attention for COVID-19 patients. The aim of this review was to collect any article considering the three conditions (HIV, TB, and SARS-CoV-2), included in PubMed/Medline and published in the English language since the beginning of the COVID-19 pandemic. We focused on detailed descriptions of the unusual cases describing the three co-infections. Eighty-four out of 184 publications retrieved met our inclusion criteria, but only three of them reported cases (five in total) with the three concomitant infections. The clinical evolution, management, and therapy of all of them were not different from mild/severe cases with exclusive COVID-19; the outcome was not worse either, with recovery for the five patients. Cases of patients with COVID-19 besides HIV and TB infections are scarce in literature, but studies deliberately embracing the triple infection as a priori inclusion criterion should be carried out in order to provide a complete understanding of joint influence.
Keywords: Epidemias; Infecciones; COVID-19; HIV; SARS-CoV-2; Coinfection; Triple-infection; Tuberculosis